Investigation of the Physicochemical Properties of Vegetable Oils Blended with Sesame Oil and Their Oxidative Stability during Frying - Fereshteh Ramroudi; Seyed Ali Yasini Ardakani; Arefeh Dehghani-tafti; Elham Khalili Sadrabad (International Journal of Food Science)
To investigate the antioxidant activity and physicochemical properties of oil, sunflower (SFO) and corn oil (CO) and their combinations with sesame oil (SO) were prepared. The analyses of fatty acid composition (GC-FID), oxidative stability index (Rancimat), smoke point, and antioxidant activity (DPPH) were done on oil samples. Then, the frying process in presence of potato chips was done for 3 days at 180°C. Oil samples were gathered after each frying cycle and chemical analysis (peroxide value, free fatty acid, p-anisidine value, TOTOX, total polar content, TBARS, and conjugated diene and triene) was measured. The major fatty acid composition of oil samples was linoleic acid, oleic acid, palmitic acid, and stearic acid. The OSI of oil samples was reported as CSO>SSO>SO>CO>SFO. The smoke point of all samples was in the standard limit. The SFO with 266.50°C had the highest smoke point. The antioxidant activity of samples was reported as SO>CSO>CO>SSO>SFO. The IC50 of SO was 52.17 mg/g which was higher than other samples. The result of frying indicated that prolonged heating process would increase the thermal oxidation. It was shown that oils blended with SO had good stability during deep frying. Therefore, blending oil with SO is considered as an economic approach to improve the oil oxidation stability.